The 99's : women aviators [videorecording (VHS)] (KSPS Public Television, 1997)
Profiles the extraordinary history of women pilots of the Inland Northwest who trace their roots back to an organization that started with 99 women in 1929, and is now over 6,000-strong. Take to the sky with them, and learn their amazing and inspiring stories.